Internet Access and the Potential in Facilitating Online Political Communication of Disabled - Nurul Hasfi; Joyo NS Gono; Wiwid Noor Rakhmad (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2020)
Researchers defined Internet as a medium for overcoming the social exclusion of marginal groups, including the disabled. The increasing of the internet penetration in Indonesia should be an opportunity for the group to build inclusive elections. However, in the Indonesian context, non-disabled still controls virtual political space. This paper identifies the potential of the internet as a means of online political participation of disabled groups. Using the case study method in the context of 2018 Central Java Pilgub, researchers conducted in-depth interviews with the disabled, election organizers and disabled educational institutions in the Semarang city. The findings of the study indicate that certain diffables (physical, deaf and mild disabilities) have access to the internet, however there is no access to the interactive political communication. The internet has not functioned optimally as an Assistive Technology (AT) mainly caused by digital divide; skepticism to the internet and limited internet literacy.